Lysozyme amyloidosis – a case report and review of the literature - Pleyer, Christopher (Clin Nephrol Case Stud, 2015)
Lysozyme amyloidosis is an exceedingly rare hereditary autosomal dominant amyloidosis, which is characterized by the precipitation of lysozyme protein within the body, leading to multi-organ dysfunction. Herein, we present the case of a U.S. family affected by lysozyme amyloidosis. In particular, we report pericardial disease involvement leading to recurrent pericardial effusion, which to our knowledge has not been described yet. To our knowledge, we have also for the first time identified the amyloidogenic component of lysozyme amyloidosis via laser microdissection and mass spectrometry from a bone marrow biopsy. The diagnosis of this disease remains challenging as it can be easily mistaken for primary amyloidosis, which also presents with similar symptoms. Immunohistochemical staining of tissue for specific amyloidogenic proteins allows for an accurate diagnosis and should be performed in all amyloidosis patients in order to spare patients from potentially futile or harmful therapy. The widespread systemic involvement of lysozyme amyloidosis currently provides limited options for treatment, although kidney and/or liver transplantation appear to be promising palliative treatments. Practicing clinicians and researchers need to collect more information about this rare entity to further characterize the behavior of this disease and develop new potential treatment strategies.